Pengembangan Buku Saku Interaktif Kata Heian Godan sebagai Media Pembelajaran Karate - Maulana, Muhammad Thomas; Arifah Kaharina (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This research departs from the need for more effective and interesting learning media in Karate learning, especially in the mastery of the Heian Godan Word which is often an obstacle for beginner students. The purpose of this study is to determine the feasibility of interactive pocket books, said Heian Godan, as a Karate learning medium. This research uses a research and development (R&D) model through the ADDIE approach which includes the stages of Analysis, Design, Development, Implementation, Evaluation. In the Analysis stage, the researcher conducts observations and interviews with extracurricular students and coaches. In this stage of design, the researcher made an interactive pocket book design Kata Heian Godan. In the Development stage, the researcher tested the product validation to 3 experts with a total average score of 93.7%, so that the product was declared suitable for use as a learning medium. In this stage of implementation, the researcher conducted a small-scale product trial on 14 Karate extracurricular students at SMK Antartika with a respondent questionnaire result of 93.2%. The Evaluation stage, reviews the feasibility of this media after expert validation tests and product trials. Based on these results, the interactive pocket book Kata Heian Godan was declared valid and feasible so that it can be used as a Karate learning medium in schools.